Sistem Informasi Penjualan Kain Batik Faizah Kota Pinang Berbasis Web - Hutagaol, Sofhia Martha (Journal of Computer Science and Information System(JCoInS), 2020)
This information system design goal is to spread and to offer Internet-based bedding. Earlier, at this store in selling its products is still manual. Because customers or buyers come directly to the store to choose and buy the products they want. It also purchases and reports sales are still done manually, so it does not make effective for the buyer or the seller.